CpG island chromatin: a platform for gene regulation. - Blackledge, N; Klose, R (2011)
The majority of mammalian gene promoters are encompassed within regions of the genome called CpG islands that have an elevated level of non-methylated CpG dinucleotides. Despite over 20 years of study, the precise mechanisms by which CpG islands contribute to regulatory element function remain poorly understood. Recently it has been demonstrated that specific histone modifying enzymes are recruited directly to CpG islands through recognition of non-methylated CpG dinucleotide sequence. These enzymes then impose unique chromatin architecture on CpG islands that distinguish them from the surrounding genome. In the context of this work we discuss how CpG island elements may contribute to the function of gene regulatory elements through the utilization of chromatin and epigenetic processes.